Criminological Analysis of LGBT Acts Committed by Unscrupulous Soldiers - Saadi, Anwar; Sugianto, Sugianto; Usman, Usman (Ann Publisher, 2024)
Today, there is a phenomenon of deviation in the behavior of social life of the community known as Lesbian, Gay, Bisexual, and Transgender (LGBT). It is strongly felt that the pattern of life in the LGBT phenomenon is a deviation from the social norms, religion, and ideology of Pancasila. From the aspect of positive law, no law can be applied to punish perpetrators of LGBT acts. What comes to the surface is precisely the pros and cons of the perspective on LGBT acts, whether they are included in the issue of violations of the law, are part of human rights, or deviations of social behavior, or just deviations of sexual orientation. Pro-LGBT groups stated that there should be no discrimination against LGBT groups, whether men, women, transgender, opposite-sex lovers, or same-sex lovers, because it is considered a human right. For the contra group to have a criminological point of view that LGBT acts are violations of the law, not part of human rights aspects, LGBT is a violation of standard norms of life, contrary to morals and ethics, is a sin according to religion, and is a threat to the cultural and ideological values of a nation. LGBT acts also occur by TNI soldiers. Lawmakers must be able to formulate the rule of law in providing guarantees of certainty, justice, and benefit for the Indonesian people in overcoming LGBT developments that are a threat to the life of the Indonesian nation. LGBT perpetrators of TNI Soldiers must be given strict sanctions because these actions are contrary to the code of ethics of TNI Sapta Marga Soldiers and the Soldier's Oath.